A new species of Coccomyces on Cunninghamia lanceolata and its phylogenetic placement based on multi-gene analysis - Lv, Tu; Hou, Cheng-Lin (Phytotaxa, 2019)
Specimens of Coccomyces collected on Cunninghamia lanceolata in Anhui Province, China were identified as a new species and named Coccomyces anhuiensis. This is the third Coccomyces species on needles of conifers. A multi-gene phylogenetic analysis showed that the new species is closely related to Coccomyces dentatus. Specimens studied are deposited in the Herbarium of the College of Life Science, Capital Normal University, Beijing, China (BJTC).